Collecting - Dobkin, Bonnie; Hackney, Rick (Chicago : Childrens Press, 1993)
An avid collector enumerates all the things that have been collected, from twenty-three keychains and fifty-one shells to a ball of tin foil five feet wide.
1.8
2.
K-3
P-2.
Keywords: Collectors and collecting -- Fiction; Stories in rhyme; Collectors and collecting -- Fiction; Stories in rhyme; Readers (Elementary).